Mykola Oleksiyovich Korzh - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The article is dedicated to the famous Ukrainian orthopedist-traumatologist, doctor of medical sciences, professor Korzh Nikolay Alekseevich, who celebrated his 70th birthday on August 12, 2017.